Importance of Cultural Legitimacy to the Local Government in Indonesian Democracy - Yunus, Rabin; Tamma, Sukri (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
This paper aims to analyze the importance of legitimacy aspect for a government, related to the existence of indigenous people, in the context of local election as the manifestation of democracy. Generally, legitimacy is interpreted in a normative understanding, particularly in its relation to the legal fulfillment of formal requirements that produces a legitimate government. Legitimacy is required to ensure that a government has justifications to implement all of its functions. Moreover, legitimacy is also necessary to ensure the compliance and support of people. Nevertheless, in terms of indigenous peoples, though formal legitimacy is indeed important, it is not the only legitimacy required by the local government. The legitimacy shall also be related to local values upheld by people. Based on the research conducted on the Toraja ethnic group in Tana Toraja, in the perspective of legal pluralism, there are two crucial intersecting governing norms. This study shows the importance of adat values to obtain legitimacy, in the context democratization in Indonesia, and the existence of adat in the implementation of local autonomy. By using several different principles as the bases, the existence of adat and formal law in the implementation of local election show that there is a collaboration effort to make the process of democracy and adat go along well, conferring a legitimacy for the local government despite the uniqueness of the Toraja people.